Biogeographic, stratigraphic, and environmental distribution of Basilosaurus (Mammalia, Cetacea) in North America with a review of the late Eocene shoreline in the southeastern coastal plain. (March 2022) - Smith, Kathlyn M.; Hastings, Alexander K.; Bebej, Ryan M.; Uhen, Mark D.
Abstract: A new specimen of Basilosaurus cetoides was discovered on the banks of the Flint River in Albany, Georgia, USA, in 2010. This fossil, which was the most complete specimen of the species from Georgia to date, consisted of five nearly complete and two partial post-thoracic vertebrae, tentatively identified as S4 through Ca6. During excavation, however, the site was looted and most of the specimen was lost to science. Nonetheless, we use this discovery as an opportunity to update the current state of knowledge on the stratigraphic, biogeographic, and environmental distribution of Basilosaurus in North America, as well as the position of the late Eocene shoreline in the southeastern United States. The results show that Basilosaurus was most abundant across the southeastern coastal plain during the early to middle Priabonian, coincident with the late Eocene maximum marine transgression. The decline in Basilosaurus localities is associated with the retreating shoreline of the terminal Eocene. The majority of Basilosaurus localities fall well south of the position of the late Eocene shoreline hypothesized in this study, suggesting the genus favored middle to outer neritic zones of the epicontinental sea. The comparatively low number of Priabonian specimens in the Atlantic Coastal Plain versus the Gulf Coastal Plain, then, suggests the presence of shallow zones in the Atlantic Coastal Plain that may have limited the distribution of Basilosaurus across the region. The hypothesized shoreline of this study ultimately differs from earlier reconstructions by extending the Mississippi embayment at the Bartonian/Priabonian boundary farther north than previously noted.